Bio-based composite of stereocomplex polylactide and cellulose nanowhiskers - Purnama, Purba; Kim, Soo Hyun (ELSEVIER SCI LTD, 2014)
The advanced bio-based composite of stereocomplex polylactide containing cellulose nanowhiskers was successfully prepared by supercritical fluid technology. This bio-stereocomplex nanocomposite material was produced by stereocomplexation of polylactide-graftcellulose nanowhishkers through supercritical carbon dioxide dichloromethane at 65 degrees C and 350 bar. The bio-stereocomplex nanocomposite polylactide was obtained in high stereocomplex degree (100%). The bio-stereocomplex nanocomposite polylactide exhibits excellent stereocomplex memory which is the main limitation of linear stereocomplex polylactide. It also shows improvement in mechanical properties up to 2.70 GPa (Young's modulus) and thermal degradation temperature. The combination of stereocomplex and nanocomposite approaches offers simultaneous improvement on physical properties. The bio-stereocomplex nanocomposite polylactide is promising material in the future to replace petroleum-based polymer as eco-friendly materials. (C) 2014 Elsevier Ltd. All rights reserved.
Keywords: HIGH-MOLECULAR-WEIGHT; SILICATE NANOCOMPOSITES; SUPERCRITICAL-FLUID; POLY(LACTIC ACID)S; MELT STABILITY; POLYMERIZATION; NANOCRYSTALS; DEGRADATION; POLYMERS; PLA